Potencial de uso de gramíneas como substrato pasteurizado no cultivo do cogumelo Pleurotus ostreatus (Jacq.) P. Kumm - Vieira, Fabrício Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
O cultivo de cogumelos comestíveis e medicinais pode ser realizado em diversos substratos liginocelulósico em sistema axênico e pasteurizado. O gênero Pleurotus é conhecido principalmente pela espécie Pleurotus ostreatus conhecido popularmente como cogumelo ostra, shimeji ou hiratake. Neste trabalho, investigou-se a variabilidade genética de quatro linhagens de Pleurotus ostreatus pela técnica RAPD, o crescimento micelial em meio de cultura sólido, parâmetros da compostagem (umidade do substrato, dinâmica da relação C/N, pH, perda de massa fresca, celulose, hemicelulose, lignina, proteína total e fibra total), produtividade, eficiência biológica e qualidade nutricional dos basidiomas (proteína total, fibra total e extrato etéreo) cultivados nos diferentes substratos em duas relações C/N. As linhagens de P. ostreatus foram coletadas de produtores do Estado de São Paulo e os materiais utilizados para a elaboração dos substratos de cultivo foram: capim braquiária, capim tobiatã, capim brizantha, palha de cana-de-açúcar, palha de trigo, bagaço de cana-de-açúcar e farelo de trigo. No primeiro experimento foi avaliado a variabilidade genética pela técnica RAPD das quatro linhagens de P. ostreatus coletadas de produtores do Estado de São Paulo. Assim foram divididos em dois grupos distintos, o primeiro grupo com as linhagens POS 09/100, POS 09/101 e POS 09/102 e o segundo grupo com a linhagem POS 98/38. Sendo que dentro do primeiro grupo as linhagens POS 09/100 e POS 09/101 apresentaram similaridade de 93%, ainda...

The cultivation of edible and medicinal mushrooms can be accomplished on various lignocellulosic substrates in system axenic or pasteurized. The Pleurotus genus is mainly known by the species as Pleurotus ostreatus popularly known oyster mushroom, shimeji or hiratake. In this study, we investigated the genetic variability of four strains of Pleurotus ostreatus by RAPD, the mycelial growth on solid medium, composting parameters (substrate moisture, dynamics of C/N ratio, pH, weight loss, cellulose, hemicellulose, lignin, total protein and total fiber), productivity and nutritional quality of mushrooms (total protein, total fiber and lipids) grown on different substrates in two C/N ratio. The strains of P. ostreatus were collected from producers of São Paulo State and the materials used for the preparation of substrates were: brachiaria grass, tobiatã grass, brizantha grass, sugar cane straw, wheat straw, sugar cane bagasse and wheat bran. In the first experiment evaluated the genetic variability by RAPD of four strains of P. ostreatus collected from producers of São Paulo State. So were divided into two distinct groups: the first group with the strains POS 09/100, POS 09/101 and 09/102 and the second group with the strain POS 98/38. Since the first group within the strains POS 09/100 and POS 09/101 showed similarly of 69% over the two aforementioned strains. In second group the strain POS 98/38 showed similarity of 36% compared to with the first group. In the second experiment evaluated the mycelial growth in culture media based on the substrate collected at the end of Phase II composting. Was used the punctuation in defined time periods (24 hours) to determine colony growth and non-parametric method of Stundent- Newman-Kills for transforming the values in growth curves higher growth rates were obtained on... (Complete abstract click electronic access below)
Keywords: Cogumelos - Cultivo; Gramínea; Substratos; Pasteurização; Palha - Utilização; Pasteurization; Plant growing media